Analisis Modal Usaha Pada Dinas Koperasi dan UKM Kabupaten Karawang - Rizkia Izriani Maliek; Dedi Mulyadi; Santi Pertiwi Hari Sandi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine how to apply for and provide business capital by the Karawang Regency Cooperative and UKM Office, as well as how the benefits obtained by MSME actors from business capital assistance provided by the Karawang Regency Cooperative and UKM Office. The research was conducted using a qualitative method, namely data collection was carried out by interviewing 30 MSME actors from various types of businesses including food vendors, salon services, clothing sewing services, screen printing services and workshop services. The form of assistance provided is in the form of minibooths, sewing machines, cooking utensils, screen printing tools, carts, salon tools and workshop tools. These 30 respondents are random sampling taken from all aid recipients from 30 sub-districts, especially those in the category of extreme poverty sub-districts. The Office of Cooperatives and SMEs previously provided assistance in the form of cash funds, but starting in 2021 plans assistance in the form of capital goods, and can be realized in 2022. From several types of assistance that have been provided by the Office of Cooperatives and SMEs to 30 respondents, it is stated that this assistance is very beneficial for business actors, both beginners and advanced, these benefits include accelerating production, reducing operational costs, better and tidier sales displays as felt by recipients of minibooth and cart assistance. The result of this research is that the utilization of capital provided by the Office of Cooperatives and SMEs has a positive impact on the business success of MSME actors in Karawang Regency. With capital that can be used for various purposes, MSME players have greater opportunities to develop and improve the quality of their products.